2015
DOI: 10.4081/rio.2015.136
|View full text |Cite
|
Sign up to set email alerts
|

Waders (Aves, Charadriiformes) in a Mediterranean remnant wetland: a year-round pilot study evidences contrasting patterns in diversity metrics

Abstract: -Around a yearly cycle (August 2011 -July 2012), we studied the assemblages of waders (Aves Charadriiformes) occurring in a Mediterranean remnant wetland, obtaining a set of diversity metrics. Mean total abundance shows a complementary pattern when compared to species richness and diversity: the highest values of mean total abundance were observed in December-January, due to high dominance of only one very abundant and gregarious species (the lapwing Vanellus vanellus). On the contrary, in this period, species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…at this time of the year, especially during and after periodic flooding, floodplain meadows provide feeding grounds for these birds; they were often observed eating small invertebrates picked out of meadows, mudflat or exposed soil. Most of these species have declined significantly in recent years and are now classified as 'of conservation concern' (Battisti et al, 2015). This guild undergoes the previous scenario, it comprised specialist species that were highly concentrated in small area (FLM represents 11.34% of the wetland surface) and have an increasing niche overlaps, which could render them more prone to habitat fluctuations and interspecific competitions.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…at this time of the year, especially during and after periodic flooding, floodplain meadows provide feeding grounds for these birds; they were often observed eating small invertebrates picked out of meadows, mudflat or exposed soil. Most of these species have declined significantly in recent years and are now classified as 'of conservation concern' (Battisti et al, 2015). This guild undergoes the previous scenario, it comprised specialist species that were highly concentrated in small area (FLM represents 11.34% of the wetland surface) and have an increasing niche overlaps, which could render them more prone to habitat fluctuations and interspecific competitions.…”
Section: Discussionmentioning
confidence: 98%
“…3). Several studies suggested that floodplain meadows provide a rich habitat for a range of shorebirds and other long-legged wading birds throughout the wintering season, particularly where there are areas of scrub or hedgerows on the drier ground (Brazner, Hoffman, 1991;Burger et al, 1997;Battisti et al, 2015). at this time of the year, especially during and after periodic flooding, floodplain meadows provide feeding grounds for these birds; they were often observed eating small invertebrates picked out of meadows, mudflat or exposed soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pluvialis squatarola (Linnaeus, 1758) M irr, W irr Lorenzetti & Taffon, 2007;Battisti et al, 2009a;Malavasi et al, 2009aMalavasi et al, , 2009bBattisti et al, 2012a;Battisti, 2014b;Battisti et al, 2015a Pluvialis apricaria (Linnaeus, 1758) M irr, W irr Max 150, 7.2.2004, R. Gildi, V. Dundee; W reg in the neighbouring areas (Macchiatonda); Battisti et al, 2015aBattisti et al, , 2016a Eudromias morinellus (Linnaeus, 1758) A 23.9.2005, M. Biondi, R. Gildi; Charadrius hiaticula Linnaeus, 1758 M reg, W irr Battisti et al, 2009a;Malavasi et al, 2009aMalavasi et al, , 2009bBattisti et al, 2015aBattisti et al, , 2019b Charadrius dubius Scopoli, 1786 M reg, B, W irr Biondi & Pietrelli, 1999;Battisti, 2006b;Causarano et al, 2006;Lorenzetti & Taffon, 2007;Fortunati & Battisti, 2008;Biondi & Pietrelli, 2009;Sozio & Battisti, 2009;Battisti et al, , 2012aBattisti, 2014b;Fraticelli, 2014;Battisti et al, 2015aBattisti et al, , 2016aBattisti et al, , 2018aBattisti et al, , 2020b Charadrius alexandrinus Linnaeus, 1758 M reg, W, B irr EN Lorenzetti & Taffon, 2007;Biondi & Pietrelli, 2009;Battisti et al, , 2012aPietrelli & Biondi, 2012;Battisti, 2014b;Biondi et al, 2014;Battisti et al, 2015a;Biondi et al, 2016;Pietrelli et al, 2016;…”
Section: Charadriidaeunclassified